Formula for a Comprehensive Year Four Student-Run Free Clinic Elective - LaJeunesse, Christopher; Bains, Ashika; Fisher, Rebecca; Chadwell, Margit; Binienda, Juliann (Journal of Student-Run Clinics, 2016)
Many student-run clinics offer electives for professional students. They provide additional clinical experience and exposure to practice management. Since it began five years ago, Wayne State University School of Medicine’s Robert R. Frank Student-Run Free Clinic offers its fourth-year medical students with an innovative and comprehensive elective. Twenty-five students have completed this elective. Four pillars create the foundation of this unique learning environment: clinical care, leadership/mentorship, teaching, and scholarship. We present a blueprint for professional schools to shape their elective to become truly student-run and to give advanced students a rich capstone experience preparing them for future training.